Renewables for supporting supply adequacy in Colombia. (15th January 2022) - Zapata, Sebastian; Castaneda, Monica; Aristizabal, Andres J.; Dyner, Isaac
Abstract: This paper aims to provide a better understanding of the impact of the rapid and large-scale inclusion of renewables in electricity markets. This depends significantly on the initial technology composition of each market. For instance, when there is a large hydroelectricity component, with significant reservoir capacity (i.e., storage capability that behaves as a battery to the system), the inclusion of renewables can apparently be achieved more quickly, and further it seems that a secure and low-cost transition to a 100% renewable power system can be achieved. A computational model was implemented for policy analysis of alternative capacity expansion scenarios, particularly seeking supply adequacy in the Colombian electricity context. This paper concludes that by 2035 a 100% renewable power system is feasible in Colombia, and that the complementarity between hydro, solar and wind energies is key for achieving supply adequacy – and without the need for fossil fuel facilities as a backup . Highlights: Hydropower systems can improve security of supply through diversification. Hydro, wind and solar power may achieve high levels of renewable penetration. Complementarity between renewables helps to achieve a power system that is 100% clean. Supply adequacy may be attained quickly and cost-effectively with renewables.